Australian adult smokers' responses to plain packaging with larger graphic health warnings 1 year after implementation: results from a national cross-sectional tracking survey. (25th February 2015) - Wakefield, Melanie; Coomber, Kerri; Zacher, Meghan; Durkin, Sarah; Brennan, Emily; Scollo, Michelle
Abstract : Background: We assessed whether the Australian plain packs with larger graphic health warnings (GHWs) achieved three specific objectives of reducing the appeal of tobacco, increasing health warning effectiveness and reducing the ability of packaging to mislead about smoking harms. Methods: We compared responses from continuous cross-sectional telephone surveys of n=2176 cigarette smokers during pre-plain packaging (April–September 2012, pre-PP) with n=759 surveyed in the transition period (October–November 2012) and n=4240 during the first year of implementation (December 2012–November 2013, PP year 1), using multivariate logistic regression analyses. Results: From pre-PP to PP year 1, more smokers disliked their pack (p<0.001), perceived lower pack appeal (p<0.001), lower cigarette quality (p<0.001), lower satisfaction (p<0.001) and lower value (p<0.001) and disagreed brands differed in prestige (p=0.003). There was no change in perceived differences in taste of different brands. More smokers noticed GHWs (p<0.001), attributed much motivation to quit to GHWs (p<0.001), avoided specific GHWs when purchasing (p<0.001), and covered packs (p<0.001), with no change in perceived exaggeration of harms. PP year 1 saw an increased proportion believing that brands do not differ in harmfulness (p=0.004), but no change in the belief that variants do not differ in strength or the perceived harmfulness of cigarettes compared with a year ago. Interactions signified greater change for four outcomes assessing aspects of appeal among young adults and two appeal outcomes among mid-aged adults. Conclusions: The specific objectives of plain packaging were achieved and generally sustained among adult smokers up to 12 months after implementation.